THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND THEIR ABILITY IN WRITING FUNCTIONAL TEXT AT SMAN 1 BANDAR LAMPUNG - TUBAGUS ZAM ZAM AL ARIF (Universitas Jambi, 2017)
This descriptive quantitative study was conducted to gather information on the correlation between students’ vocabulary mastery and their ability in writing functional text. Based on the preliminary study found that there are many problem faced by the students especially in writing. Many students still find difficulties to make composition based on their own words, and express their idea, felling, thought messages in written correctly. Meanwhile, improving writing skill should be supported by mastering vocabulary. Vocabulary is important in writing because without vocabulary the students will face difficulties in writing especially in writing functional text. This research was conducted on the tenth grade students at SMA Negeri 1 Bandar Lampung. This study was conducted to determine the correlation between students’ vocabulary mastery and their ability in writing functional text. In collecting the data, the writer used objective test that were multiple choice consisted of 50 items and writing functional text test. In this research, product moment used to analyze the data of the research. The result of the data analysis showed that rcount = 0.54 it means there is correlation between students’ vocabulary mastery and their ability in writing functional text. The rcount=0.58 is higher than rtable with n=40 on significant 5% = 0.312. It means that there was a correlation between students’ vocabulary mastery and their ability in writing functional text, so the hypothesis could be proved. By the criterion if rcount = 0,58 it means that the correlation is sufficient.